2022
DOI: 10.1098/rsob.210305
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput assay for directly monitoring nucleolar rRNA biogenesis

Abstract: Studies of the regulation of nucleolar function are critical for ascertaining clearer insights into the basic biological underpinnings of ribosome biogenesis (RB), and for future development of therapeutics to treat cancer and ribosomopathies. A number of high-throughput primary assays based on morphological alterations of the nucleolus can indirectly identify hits affecting RB. However, there is a need for a more direct high-throughput assay for a nucleolar function to further evaluate hits. Previous reports … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 117 publications
10
47
0
Order By: Relevance
“…Strikingly, cells depleted of RSL24D1 or PeBoW components exhibited a strong reduction in nucleolar rRNA biogenesis relative to siNT and siSBDS negative control cells (Fig. 3C, D), consistent with previous results following depletion of Ribi factors required for both pre-rRNA processing and transcription (Bryant et al 2022). Taken together, these results indicate that RSL24D1 and PeBoW modulate rDNA transcription, linking LSU processing factors to RNAPI transcription regulation.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Strikingly, cells depleted of RSL24D1 or PeBoW components exhibited a strong reduction in nucleolar rRNA biogenesis relative to siNT and siSBDS negative control cells (Fig. 3C, D), consistent with previous results following depletion of Ribi factors required for both pre-rRNA processing and transcription (Bryant et al 2022). Taken together, these results indicate that RSL24D1 and PeBoW modulate rDNA transcription, linking LSU processing factors to RNAPI transcription regulation.…”
Section: Resultssupporting
confidence: 91%
“…3B). This result was further corroborated by in cellulo pulse labeling with the uridine analogue 5-ethynyl uridine (5-EU) and the analysis of its incorporation into nascent nucleolar rRNA through immunofluorescent staining as in (Bryant et al 2022). Strikingly, cells depleted of RSL24D1 or PeBoW components exhibited a strong reduction in nucleolar rRNA biogenesis relative to siNT and siSBDS negative control cells (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…This result was further corroborated by in cellula pulse labeling with the uridine analog 5-ethynyl uridine (5-EU) and the analysis of its incorporation into nascent nucleolar rRNA through immunofluorescent staining as in (Bryant et al 2022). Strikingly, cells depleted of RSL24D1 or PeBoW components exhibited a strong reduction in nucleolar rRNA biogenesis relative to siNT and siSBDS negative control cells (Fig.…”
Section: Rsl24d1 and The Pebow Complex Are Required For Rnapi Promote...supporting
confidence: 52%
“…We therefore examined whether alt-LAMA3 affects rDNA transcription as well. Using a miniaturized 5-ethynyl uridine (5-EU) assay for nucleolar rRNA transcription (Hayashi et al, 2018;Ogawa et al, 2021;Stamatopoulou et al, 2018;Bryant et al, 2022), we found a significant defect in pre-rRNA synthesis in alt-LAMA3 KO cells (Figures 3E and S3I). Utilizing a dual-luciferase reporter (Ghoshal et al, 2004;Sondalle et al, 2019), we observed a defect in RNA polymerase I (RNAPI) transcription in the absence of alt-LAMA3 ll Resource (Figure 3F).…”
Section: Llmentioning
confidence: 99%